2022
DOI: 10.1212/wnl.0000000000200771
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Targets of Antidiabetic Drugs and Alzheimer Disease Risk

Abstract: Background and Objectives:Previous studies have highlighted anti-diabetic drugs as repurposing candidates for Alzheimer´s disease (AD), but the disease-modifying effects are still unclear.METHODS:A two-sample Mendelian randomization (MR) study design was applied to examine the association between genetic variation in the targets of four anti-diabetic drug classes and AD risk. Genetic summary statistics for blood glucose were analyzed using UK Biobank data of 326,885 participants, while summary statistics for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Finally, to evaluate the strength of the selected SNPs, the F statistics were calculated using the formula F = R 2 (N–k–1)/[(1–R 2 ) k], where R 2 is the proportion of variability explained by each SNP, N is the sample size of the GWAS, and k is the number of SNPs. When the F-statistic is <10, it indicates that IV is a weak instrument ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, to evaluate the strength of the selected SNPs, the F statistics were calculated using the formula F = R 2 (N–k–1)/[(1–R 2 ) k], where R 2 is the proportion of variability explained by each SNP, N is the sample size of the GWAS, and k is the number of SNPs. When the F-statistic is <10, it indicates that IV is a weak instrument ( 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, many studies have shown that diabetes drugs (such as metformin, sulfonylureas, and pioglitazone etc.) not only play a role in blood glycemic control, but also can impact on neuroprotection, neurogenesis, neuroinflammation, synaptic plasticity, and proteins aggregationthrough different mechanisms and linking pathways, in order to reduce the risk of suffering from AD [39][40][41][42][43][44]. Moreover, early and effective control of hyperglycemia has a positive impact on reducing the risk of AD and delaying the progress of AD, and neurodegeneration plays an important role in this process.…”
Section: Admentioning
confidence: 99%
“…Mendelian randomization analysis is currently being used to investigate the relationship between antihypertensive drugs and psychiatric disorders 17 , drug targets for the treatment of Parkinson's disease 18 , and the risk of lipid-lowering drugs, antiglycemic drugs, and Alzheimer's disease 19,20 . In this study, to explore the effects of different antiglycemic drug treatments on epilepsy, we used the public GTEx -V8 database to con rm the proxy antiglycemic drug target genes of instrumental variables and performed two-sample Mendelian randomization analysis.…”
Section: Introductionmentioning
confidence: 99%